2023
DOI: 10.3390/ijerph20020957
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Water Variables: Review and Scientometric Analysis

Abstract: COVID-19 has changed the world since 2020, and the field of water specifically, boosting scientific productivity (in terms of published articles). This paper focuses on the influence of COVID-19 on scientific productivity with respect to four water variables: (i) wastewater, (ii) renewable water resources, (iii) freshwater withdrawal, and (iv) access to improved and safe drinking water. The field’s literature was firstly reviewed, and then the maps were built, emphasizing the strong connections between COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…According to recent studies [4,6,[30][31][32], the degree of pollution in the aquatic systems in Romania decreased with the decrease in the incidence of COVID-19 cases. Post-pandemic effects can be seen in the horizontal transmission of acquired antibiotic resistance and the perpetuation of resistant bacteria in aquatic environments, with impacts on population health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent studies [4,6,[30][31][32], the degree of pollution in the aquatic systems in Romania decreased with the decrease in the incidence of COVID-19 cases. Post-pandemic effects can be seen in the horizontal transmission of acquired antibiotic resistance and the perpetuation of resistant bacteria in aquatic environments, with impacts on population health.…”
Section: Resultsmentioning
confidence: 99%
“…Water, besides being a strategic resource for society, is an important vector in spreading infectious diseases over large areas. This was certainly the case of the COVID-19 pandemic, when water management was a major factor in SARS-CoV-2 spreading as well as its associated infections [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies [4,6,[30][31][32], the degree of pollution of the aquatic systems in Romania decreased with the decrease in the incidence of Covid-19 pandemic. Post-pandemic effects can be seen in the horizontal transmission of acquired antibiotic resistance and the perpetuation of resistant bacteria in aquatic environments with impacts on population health.…”
Section: Amentioning
confidence: 99%
“…Water, besides being a strategic resource for society, is an important vector in spreading infectious diseases over large areas. Certainly, it was the case of Covid-19 pandemic when the water management was a major factor in SARS-CoV-2 virus spreading as well as its associated infections [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mean precipitation has been found to affect public opinion, with areas experiencing drought having a negative impact on public opinion (Lee et al, 2019; Savari et al, 2022). Furthermore, safe drinking water services and annual freshwater withdrawal for domestic use have also been identified as factors affecting public opinion (Mare et al, 2023; Voulvoulis, 2018). Finally, annual freshwater withdrawal for agriculture and industrial use has also been found to influence public opinion (Rogers et al, 1998; Wade Miller & Miller, 2006).…”
Section: Introductionmentioning
confidence: 99%